2018
DOI: 10.1002/ajb2.1186
|View full text |Cite
|
Sign up to set email alerts
|

Variations in ramet performance and the dynamics of an alpine evergreen herb,Gentiana nipponica, in different snowmelt conditions

Abstract: Citation: Kawai, Y., and G. Kudo. 2018. Variations in ramet performance and the dynamics of an alpine evergreen herb, Gentiana nipponica, in different snowmelt conditions. American Journal of Botany 105(11): XXX. DOI: XXXX PREMISE OF THE STUDY: Variation in demographic parameters reflects the life-history strategies of plants in response to specific environments. We aimed to investigate the intraspecific variation in life-history traits of a clonal alpine herb, Gentiana nipponica, in various snowmelt condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In a 31-year-long phenology study in the Rocky Mountains, Inouye (2008) found a higher degree of frost damage after early snowmelt. Number of flowers, leaf growth and survival of the evergreen forb Gentiana nipponica were significantly reduced in populations with 1-month earlier snowmelt (Kawai and Kudo 2018). However, occasional frost damages do not necessarily cause a population decline, given that these taxa are all long lived and, to variable degree, clonal.…”
Section: The Role Of Snowmelt and Microclimatementioning
confidence: 94%
“…In a 31-year-long phenology study in the Rocky Mountains, Inouye (2008) found a higher degree of frost damage after early snowmelt. Number of flowers, leaf growth and survival of the evergreen forb Gentiana nipponica were significantly reduced in populations with 1-month earlier snowmelt (Kawai and Kudo 2018). However, occasional frost damages do not necessarily cause a population decline, given that these taxa are all long lived and, to variable degree, clonal.…”
Section: The Role Of Snowmelt and Microclimatementioning
confidence: 94%
“…A one-month earlier snowmelt may expand the alpine growing season by more than one third by the end of the century (RCP8.5), most likely with drastic consequences for alpine plants. These may include lower flower numbers, reduced leaf growth and a lower survival, as observed for the evergreen forb Gentiana nipponica by a one-month earlier snowmelt (Kawai and Kudo 2018), and snowbed species produced less seeds after an earlier snowmelt of 18 days (Tonin et al 2019). According to an experiment with 23 nival and alpine species, it is assumed that one third to one half the alpine flora may be sensitive to photoperiod and hence may not profit from a longer growing season because of too short daylengths (Keller and Körner 2003).…”
Section: Consequences For Alpine Plantsmentioning
confidence: 97%
“…Spatial heterogeneity, even at a relatively small scale, can produce a similar level of demographic variation within a continuous population as that between populations (Fowler & Antonovics, 1981; Horvitz & Schemske, 1995). Local scale demographic variation has been documented along the environmental gradient within populations for several plant species (Kawai & Kudo, 2018; Vega & Montaña, 2004). Local snowmelt gradients in alpine ecosystems are a crucial environmental factor responsible for diverse plant communities at the local scale (Hülber et al, 2011; Kudo & Ito, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The distributions of alpine plant species are primarily determined by the spatial heterogeneity of environmental conditions, such as snowmelt time, soil moisture, land surface stability, nutritional conditions and geological properties (Nagy & Grabherr, 2009). In particular, the spatial heterogeneity of snowmelt time, which determines the growing season length, is a crucial factor that affects the distribution pattern (Hülber, Bardy, & Dullinger, 2011; Kudo & Ito, 1992; Litaor, Williams, & Seastedt, 2008), flowering phenology (CaraDonna, Iler, & Inouye, 2014; Kudo, 2016), leaf physiology (Choler, 2005; Kudo, Nordenhäll, & Molau, 1999; Wheeler et al, 2014), reproductive output (Gezon, Inouye, & Irwin, 2016; Kudo & Hirao, 2006; Lluent, Anadon‐Rosell, Ninot, Grau, & Carrillo, 2013; Moriwaki, Takyu, & Kameyama, 2020) and demographic parameters of alpine plants (Campbell, 2019; Hülber et al, 2011; Kawai & Kudo, 2018). Therefore, snowmelt time advancement due to global warming may lead to changes in population dynamics, distribution shifts and/or the local extinction of alpine plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation